Synthesis of novel, DNA binding heterocyclic dehydroabietylamine derivatives as potential antiproliferative and apoptosis-inducing agents - Fengyi Zhao; Xu Sun; Wen Lu; Li Xu; Jiuzhou Shi; Shilong Yang; Mengyi Zhou; Fan Su; Feng Lin; Fuliang Cao (Taylor & Francis Group, 2020)
Several dehydroabietylamine derivatives containing heterocyclic moieties such as thiophene and pyrazine ring were successfully synthesized. The antiproliferative activities of these thiophene-based Schiff-bases, thiophene amides, and pyrazine amides were investigated in vitro against Hela (cervix), MCF-7 (breast), A549 (lung), HepG2 (liver), and HUVEC (umbilical vein) cells by MTT assay. The toxicity of L1−L10 (IC50 = 5.92− >100 μM) was lower than L0 (1.27 μM) and DOX (4.40 μM) in every case. Compound L1 had higher anti-HepG2 (0.66 μM), anti-MCF-7 (5.33 μM), and anti-A549 (2.11 μM) and compound L3 had higher anti-HepG2 (1.63 μM) and anti-MCF-7 (2.65 μM) activities. Both of these compounds were recognized with high efficiency in apoptosis induction in HepG2 cells and intercalated binding modes with DNA. Moreover, with average IC50 values of 0.66 and 5.98 μM, L1 was nine times more effective at suppressing cultured HepG2 cells viability than normal cells (SI = 9). The relative tumor proliferation rate (T/C) was 38.6%, the tumor inhibition rate was up to 61.2%, which indicated that L1 had no significant toxicity but high anti-HepG2 activity in vivo. Thus, it may be a potential antiproliferation drug with nontoxic side effects.